FRI0114 Allograft inflammatory factor 1 (AIF1) polymorphisms RS4711274 (G/A) and RS2269475 (C/T) may predict etanercept plus methotrexate response in french caucasian patients with rheumatoid arthritis. (15th June 2017) - Azzouz, DF; Haddad, M El; Kanaan, S; Balandraud, N; Martin, M; Picard, C; Roudier, J; Auger, I; Lambert, NC
Abstract : Background: Several risk loci for Rheumatoid Arthritis (RA) have been identified by Genome Wide Association Studies (GWAS), but they do not include Allograft Inflammatory Factor 1 (AIF1). Nevertheless, a few studies have shown that AIF1 rs2269475 (C/T) is associated with RA 1, 2 . Objectives: We propose 1) To examine associations in French Caucasian patients with RA, of the seven most described AIF1 SNPs; 2) To study their linkage disequilibrium with HLA-DRB1 alleles; 3) To evaluate whether AIF1 single nucleotide polymorphisms (SNPs) could predict first line treatment responses in RA. Methods: We amplified the AIF1 gene region containing the 7 SNPs and sequenced PCR products on a total of 469 individuals, including 95 Anti-Citrullinated Protein Antibody (ACPA) positive RA patients, 146, patients with scleroderma, 132 healthy controls and 96 additional healthy controls selected from a large database of volunteer bone marrow donors (VBMD) for carrying at least one RA-associated allele. Patients and controls were HLA-DRB1 genotyped. Patients with RA were divided into 2 groups, a first group called " non responders " was defined as patients who did not respond to first-line methotrexate (MTX) combined with Etanercept and a second group called " good responders " was defined as patients who did respond to methotrexate combined with Etanercept. Results: Two SNPs were associated with RA: rs4711274 (G/A) and rs2269475 (C/T) . The frequency of minor allele carriers was respectively 37% (A) and 36% (T) in patients with RA versus 18% among controls (p=0.0014 and p=0.001). Furthermore, patients with RA-associated HLA-DRB1 alleles carried more often minor alleles for both SNPs (p=0.0005). Preliminary clinical data show that 56% of non-responders (N=16) carried the minor alleles of both rs4711274 and rs2269475 compared to only 21% of good responders (N=24, p=0.02). Conclusions: AIF is an inflammation-responsive protein encoded within the HLA class III region on chromosome 6 (6p21.3). As already described in British and Polish Caucasians, we found a significant AIF1 Rs2269475 association with RA. We also found an association with Rs4711274 in linkage disequilibrium with the former. The increased frequency of minor AIF1 alleles in RA was not associated with a particular HLA-DRB1 allele, but to any HLA-DRB1 allele carrying the shared epitope. Finally, patients who failed to respond to Etanercept and MTX carried more often minor alleles of the 2 described AIF1 SNPs. Further analysis on a larger groups of patients is required to confirm whether AIF1 SNPs can predict response to therapy with Etanercept and Methotrexate. References: Harney SM, Vilarino-Guell C, Adamopoulos IE, Sims AM, Lawrence RW, et al. (2008) Fine mapping of the MHC Class III region demonstrates association of AIF1 and rheumatoid arthritis. Rheumatology 47: 1761–1767. Pawlik A, Kurzawski M, Szczepanik T, Dziedziejko V, Safranow K, et al. (2008) Association of allograft inflammatory factor-1 gene polymorphism with rheumatoid arthritis. Tissue antigens 72: 171–175. Disclosure of Interest: None declared